PERUBAHAN IDENTITAS PENGGUNA NARKOBA DI TEMPAT TERAPI SPIRITUAL (STUDI KOMUNIKASI TERAPEUTIK DI PONDOK INABAH II PANJALU CIAMIS) - Hermawati, Yanti (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2010)
This research based on the assumption that drug abusers are capable and aware ones to interpret spiritual therapy symbol for their healing. The interpretation is important for meaning construction process in communication. This aim research is finding out spiritual therapy process for drug abuser in Pondok Inabah II and identity change in therapy process as part of the therapeutic communication process for healing from drug addiction. The research design was qualitative method with phenomenology tradition. The subject were eight drug abuser were being therapy. The subject selected purposively by particular criteria and their readiness. The data such as statements and communication behaviors found by in depth interview, then analyzed descriptive-qualitatively. The result show that identity change of drug abuser from identity of drug abuser to ?anak bina? in Pondok Inabah II and identity of ?Ikhwan TQN?. The identity change take place three level; transition phase, initiation phase, and intensification phase. Researcher found the consciousness of drug abuser that is medical and spiritual consciousness. The identity change also shows consciousness change